Color constancy of color reproductions in art paintings - Amano, Kinjiro (2018)
Popular color reproductions of art paintings such as postcards are intended to remind viewers of the original works. It is, however, unclear how well the quality of the reproductions is preserved under various illuminations. Color constancy of the reproductions in relation to colors in the original paintings was estimated computationally with hyperspectral images of 15th-century Flemish paintings, 20th-century modern abstract paintings, and their corresponding postcards with a series of illuminants: the CIE daylight D65 with correlated color temperature (CCT) 6500 K, daylight D40, fluorescent lamps F2 and F11, and a LED lamp designed for museums with CCT approximately 3500–4000 K. Despite large colorimetric differences between the types of art paintings and between the illuminants simulated, local areas showed good color constancy: skin areas in the Flemish paintings ranged from 0.76 to 0.81, whereas nonskin areas ranged from 0.19 to 0.68. This result suggests that viewers may be able to achieve color constancy with the reproduction postcards by disregarding inconsistent colors representations from the original paintings caused by changes in illumination conditions.